Beyond Platform Adoption: Education Policy Transformation, Institutional Capacity, and Learning Effectiveness - Johansyah, Oky Nur Pratiwi; Sulmiah, Sulmiah (Pattimura University, 2026)
The integration of digital technology into education has accelerated significantly, transforming not only instructional practices but also education policy and governance frameworks. This study examines the transition from conventional to digital learning by assessing the association between technology-based education policy transformation and student learning outcomes in Ujung Pandang District, Makassar City, Indonesia. Adopting a quantitative explanatory design, data were collected through a structured survey administered to 198 students enrolled in public senior high schools that had implemented digital learning platforms. Technology-based policy transformation was operationalized through four dimensions: digital platform utilization, institutional support, teacher readiness, and digital infrastructure. Learning outcomes were measured using perceived academic performance, learning engagement, and perceived learning effectiveness. Descriptive statistics indicate that students perceived the implementation of digital learning policies at a relatively high level, particularly in terms of digital platform utilization and infrastructure availability. Inferential analysis reveals a strong and statistically significant relationship between policy transformation and learning outcomes. Regression results demonstrate that technology-based education policy transformation explains a substantial proportion of variance in learning outcomes, highlighting the importance of governance and institutional factors in shaping digital learning effectiveness. Among the policy dimensions, digital platform utilization and teacher readiness emerged as the strongest predictors. This study contributes to the literature by framing digital learning effectiveness within an education policy transformation and public administration perspective. The findings provide policy-relevant insights for local governments and education administrators seeking to strengthen the design, implementation, and sustainability of technology-based learning reforms in urban education contexts.